2001
DOI: 10.1007/s004640090006
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cholangiography in laparoscopic cholecystectomy during residency in general surgery

Abstract: Laparoscopic IC is a safe and accurate procedure for the diagnosis of unrecognized choledocholithiasis. Teaching of this procedure as part of the specialization in general surgery would be opportune because it would provide surgical residents with an additional tool for the diagnosis and treatment of this pathology of the common bile duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
3
1
3
Order By: Relevance
“…However, at our institution, where we frequently use IOC, the procedure typically adds approximately 10-15 min of additional time to a standard laparoscopic cholecystectomy. This additional time is also in agreement with the current literature, in which several recent large studies report the additional time for and IOC as being between 8 and 13 min [3,15,16]. Additionally, Ludwig et al add that, in their 2002 series out of Germany, the cost of an IOC was only 30-50 USD, compared to 100-150 USD for an additional ERCP [3].…”
Section: Discussionsupporting
confidence: 83%
“…However, at our institution, where we frequently use IOC, the procedure typically adds approximately 10-15 min of additional time to a standard laparoscopic cholecystectomy. This additional time is also in agreement with the current literature, in which several recent large studies report the additional time for and IOC as being between 8 and 13 min [3,15,16]. Additionally, Ludwig et al add that, in their 2002 series out of Germany, the cost of an IOC was only 30-50 USD, compared to 100-150 USD for an additional ERCP [3].…”
Section: Discussionsupporting
confidence: 83%
“…The success rate of IOC in this study (64% for routine, 76% for selective, 66% overall) is lower than success rates reported by others, which range from 81 8 to 99% 7 . We acknowledge that the low success rate in the present study is a potential source of bias, particularly for the routine group, for whom a higher rate of cholangiography might have detected more CBD stones and altered the results.…”
Section: Discussioncontrasting
confidence: 77%
“…Those recommending routine IOC cite the detection of unsuspected common bile duct (CBD) stones, the delineation of biliary anatomy and the reduced risk of CBD injury as reasons to perform the test 2–6 . Others favour its selective use because anatomical abnormalities and unsuspected stones are found in only 3–7% of cases 7–9 , CBD stones can pass spontaneously 10,11 and false positive cholangiograms do occur 12 . Thus routine IOC can lead to unnecessary duct exploration or endoscopic retrograde cholangiopancreatography (ERCP), each with its attendant morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Zum Zeitpunkt der Cholezystektomie ist die Prävalenz von Gallengangssteinen altersabhängig und liegt bei Patienten unter 60 Jahren zwischen 8 und 15 %, bei über 60-Jährigen zwischen 15 und 60 % [26]. Diagnostikum der ersten Wahl bei laborchemischem und sonographischem Verdacht auf eine Choledocholithiasis ist die ERC mit einer Sensitivität von 84 -89 % und einer Spezifität von 97 -100 % bezüglich des Steinnachweises [26]. Die diagnostische ERC hat dabei eine Morbidität von bis zu 10 % und eine Letalität von bis zu 1 % [15].…”
Section: Choledocholithiasisunclassified
“…Die ERC im Rahmen des "therapeutischen Splittings" kann prä-, intra-und postoperativ durchgeführt werden, und damit eine Laparotomie zur Choledochusrevision verhindern. Bei einer Clearancerate von 90 -95 % mittels therapeutischer ERC liegt die Morbidität bei 3 -15 % und die Letalität bei 0,2 -2,5 % [26,31]. Mit zunehmender Erfahrung in der transzystischen oder per Choledochotomie durchgeführten laparoskopischen Choledochusrevision haben prospektive Studien eine gleiche Erfolgsrate wie bei der ERC gezeigt [29,32]…”
Section: Choledocholithiasisunclassified